Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 3 - Section 3.2 - The Product and Quotient Rules - 3.2 Exercises: 26



Work Step by Step

$f(x)=\dfrac{ax+b}{cx+d}$ (Here, $a$, $b$, $c$ and $d$ are constants) Differentiate using the quotient rule: $f'(x)=\dfrac{(cx+d)(ax+b)'-(ax+b)(cx+d)'}{(cx+d)^{2}}=...$ $...=\dfrac{(cx+d)(a)-(ax+b)(c)}{(cx+d)^{2}}$ Simplify: $...=\dfrac{acx+ad-acx-bc}{(cx+d)^{2}}=\dfrac{ad-bc}{(cx+d)^{2}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.